Annual Report and Accounts for the year ended 30th June, 1978 (The Southern African Institute of Mining and Metallurgy, 1979)
Council and Standing Committees, 1977-1978 President: P. A. von Wielligh. Vice-Presidents: Dr M. G. Atmore and D. A. Viljoen. Honorary Treasurer: J. K. E. Douglas. Immediate Past President, Dr M. D. G. Salamon. Members of Council: J. D. Austin, A. N. Brown, A. A. Hazell, Dr P. R. Jochens, Prof. R. P. King, Dr D. G. Krige, Prof. F. Q. P. Leiding, D. G. Malan, J. C. Mostert, H. G. M. Rose, W. T. Ruhmer, A. A. Sealey, R. A. von Maltitz. Chairman, Witbank-Middelburg Branch: T. S. Wilmot. Chairman, Orange Free State-Klerksdorp Branch: A. N. Shand. Past Presidents Serving on Council: R. J. Adamson, H. Britten, J. K. E. Douglas, Prof. D. D. Howat, Dr J. P. Hugo, D. G. Maxwell, Prof. R. P. Plowman, Dr R. E. Robinson, P. W. J. van Rensburg. Standing Committee Chairmen: Membership, D. A. Vil¬joen; Technical Programme - Metallurgy, Dr P. R. Jochens ; Technical Programme - Mining, Dr D. K. Krige ; Vacation School - Metallurgy, Prof. R. P. King ; Vacation School - Mining, Dr M. D. G. Salamon; Awards, Dr M. D. G. Salamon; Excursions, Dr M. G. Atmore; Adjudication, Dr M. D. G. Salamon; Consti¬tution, Rules, and Policy, Dr M. D. G. Salamon; Mines and Works, P. A. von Wielligh ; Education, Dr M. D. G. Salamon; Monograph Series, Dr R. E. Robinson; Phoenix National Committee, Dr R. E. Robinson ; Pyrometallurgical Discussion Group Convenor, Dr J. B. See/Dr D. I. Ossin.